(untitled) (Environment & Health, 2016)
Objective. We assessed the impact of the day regimen factors on the mental working capacity in the senior pre-school age children. Materials and methods. We studied the mental working capacity on the basis of the modification of the proof methodology by M.V. Antropova, using the tables with drawings, in the senior pre-school children. The motivation readiness of a child to a systematic training was determined by Kern-Jirásek methodology. Dynamic tremor as an indicator of neuropsychical strain and, to a certain extent, a preparedness of hand for writing were studied by the "Tracks" methodology (by L. Wenger). We developed a special questionnaire for the parents on the duration of a child’s stay in the pre-school institutions, and the day regimen as well: walk duration in a free time, duration of time for computer games, watching of the TV programs, sleep duration. Conclusions. We determined that 51.4% of the senior pre-school age children spent less than 1.5 hours in the open air, 83.0% watched TV for more than 30 minutes, 41.5% played computer games, and 50.0% of the children had a sleep deficiency. Thus, the above research results indicate that the correct, age appropriate day regimen improves health, provides high working capacity, successful implementation of the various activities, prevents fatigue. At the same time the serious day regimen violations (reduction of outdoor activities, daytime sleep, self-dependent game activity, recreational measures) lead to a decrease of mental working capacity.